Conceitos de física moderna e contemporânea no ensino médio utilizando a astronomia como processo facilitador - Ramos, Patrick Luan Pacheco (2021)
This work proposes the insertion of concepts of Modern and Contemporary Physics in High School through Astronomy as a facilitator in the teaching-learning process. This proposal arose through a problem detected from the observation with students and professors in contents covered throughout the year when they taught the discipline of Physics. Concepts related to Modern Physics were not addressed, much less commented on, given the technological evolution that we are experiencing. However, it was noticed that elements of Astronomy fascinate students. Thus, it is favorable to take advantage of these “enhancers” elements for the insertion of these contents not addressed to students. This insertion took place through an Interactive Didactic Sequence, which is our educational product, with the objective of improving these concepts, as well as motivating students and demystifying erroneous concepts of colloquial use. The activities were carried out with third-year high school students at Colégio Estadual Polivalente in Santo Estevão and with some students from the private network in Feira de Santana. In the proposed activities are the contents of Solar Structure and its Evolution, Force of Nuclear Reactions, Chemical Elements and Study of Nebulae for Star Formation. Students were submitted to previous questionnaires and activities for discussions and formation of initial subsumers that anchor to the new contents addressed, as proposed by the Critical Meaningful Learning Theory. The students were able to advance in the understanding of concepts related to both Physics and Astronomy content after the production of the proposed activities, and with this it was possible to keep everyone's attention and interest when developing the activities, arousing curiosities and challenging students to make it themselves researchers as a way of learning. These results were only possible through the application of different methodologies that contribute to the teaching-learning process.